Improving the technical characteristics of a decontamination tanker with the help of TRIZ - Čabarkapa, Obrad T.; Rajić, Dušan S. (Vojnotehnički glasnik / Military Technical Courier, 2016)
This paper explains the application of the TRIZ methodology (Theory of Solving Inventive Tasks) in the field of solving a technical problem in a decontamination tanker. TRIZ is one of the most suitable scientific and innovative methodologies for solving problems, based on a systematic and logical approach, developed as a result of studying a great number of patents. The correct use of a decontamination tanker identified a harmful function related to preparing the decontamination solution in the on-board reservoir itself, which disabled the supply of drinking water.The function used to extend the use of decontamination tankers to delivery of drinking water was achieved using the Inventive Principles and Alshtuler’s Contradiction Matrix, both known to be very efficient TRIZ methodology tools.
Keywords: TRIZ methodology; harmful function; technical system; technical contradiction; contradiction matrix; inventive principles